L’arrivée de la libération gay en France. Le Front Homosexuel d’Action Révolutionnaire (FHAR) - Michael Sibalis (Genre, Sexualité et Société)
The Homosexual Front for Revolutionary Action (FHAR), founded in Paris in March 1971 by a small group of lesbians and homosexual men, marked a new direction in homosexual activism in France by breaking with the discretion and respectability preached by Arcadie, a “homophile” movement launched by André Baudry in 1954. The new homosexual activists who joined the FHAR drew their revolutionary rhetoric from left-wing militants of May 1968. They denounced “the dominant heterosexual and capitalist sexuality” and engaged in deliberately provocative actions. Their weekly meetings at the School of Fine Arts in Paris, which managed to continue for three years, turned into chaos and even gigantic orgies, and the lesbians left. The FHAR proved incapable of defending the rights of homosexuals effectively and it disappeared in February 1974. The gay associations that followed it in the 1970s and 1980s laid claim to more pragmatic methods.